Proteomic Analysis by 4D Label-free MS-PRM Provides Insight into the Role and Regulatory Mechanisms of IL-25 in NK Cells - Feng, Juan; Huang, Luoyao; Yang, Shuaipeng; Pan, Jiasheng; Zhu, Xiangxing; Tang, Dongsheng (Protein and Peptide Letters, 2023)
Background: NK cells play an important role in immune response, immune surveillance, and metabolism regulation. Therefore, NK cells are involved in the occurrence and development of various diseases, such as infectious diseases, cancer, obesity, and diabetes. IL-25 is a special member of the IL-17 family with anti-inflammatory function. IL-25 can regulate inflammatory response and metabolism via various immune cells; however, the role and regulatory mechanism of IL-25 in NK cells are still unclear.Method: In this study, we investigate the role of IL-25 in NK-cell protein profile via 4D label-free mass spectrum and validate the differential proteins via PRM analysis. In addition, GO analysis, KEGG analysis, and other bioinformatic analysis methods are used to explore the enriched function and signal pathway of differentially expressed proteins.Result and Discussion: The GO and KEGG analyses suggest that IL-25 may affect the processes, such as metabolism, thermogenesis, and oxidative phosphorylation of NK cells. There are 7 down-regulated proteins (NCR1, GZMB, PRF1, KLRC1, NDUFA11, LAMTOR5, and IKBIP) and 1 up-regulated protein (PSMD7) in IL-25-treated NK cells versus the control group for PRM validation. Our results indicate that IL-25 may regulate metabolism and other biological processes via NK cells, which will be beneficial in revealing the role and regulatory mechanisms of IL-25 in NK cells in various diseases.Conclusion: Proteomics combined with bioinformatic analysis will help to mine more information hidden behind mass spectrometry data and lay the foundation for finding clinical biomarkers and mechanisms of diseases.
Keywords: mass spectrum